Real Unit Labor Costs Differentials in EMU+L4700 : How Big, How Benign and How Reversible? - Lebrun, Igor (IMF Working Papers; Working Paper, 2011)
Real unit labor costs (RULC) growth differentials between euro area members have persisted since EMU began and even widened out in the run-up to the crisis. This paper focuses on the causes underlying such dispersion. According to our empirical findings, persistent RULC growth differentials can be attributed to divergent evolutions in capital-output ratios, nominal effective exchange rates and country-specific institutional features, coupled with an increased sensitivity of RULC to fundamentals following the shift in the monetary regime. Because these RULC growth discrepancies in EMU partly result from heterogeneous structural characteristics, policy action seeking more homogenous regulation across the euro area can make a significant contribution to reduce them.